The influence of zirconium addition on the structure and properties of Ti-2.5Al–5V-5mo alloy sheets - A. Zh Terlikbaeva; A.M. Alimzhanova; Galymzhan Maldybayev; Anar Mukhametzhanova; Banu Sakhova; Gulzada M. Koishina; Abdurassul A. Zharmenov (Case Studies in Chemical and Environmental Engineering)
This study explores the influence of zirconium (Zr) additions on the phase composition, microstructure, and mechanical properties of Ti-2.5Al–5V–5Mo alloy sheets. Through isothermal and polythermal section analysis, we quantified the phase transformations in the Ti–Al–Mo–V–Zr system under varying cooling rates. The introduction of Zr resulted in a refined duplex microstructure, significantly reducing grain size and enhancing mechanical properties. In the temperature range of 600–750 °C, the α/β-phase ratio shifted from 70/30 to 30/70, reflecting optimized phase stability. Post-rolling thermal treatments further refined the microstructure to an ultrafine grain size, which improved yield strength and tensile strength while preserving ductility. The findings demonstrate that precise control over Zr content and thermal processing parameters can achieve an ideal balance between strength and ductility, making these alloys highly suitable for advanced structural applications. This research underscores the potential of Zr-alloyed titanium alloys for industrial use, particularly where enhanced mechanical performance and microstructural stability are critical.